ANALISIS PENGARUH KECOCOKAN INDIVIDU-ORGANISASI (PERSON-ORGANIZATION FIT) TERHADAP KEINGINAN UNTUK KELUAR (TURNOVER INTENTION) DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING (Studi pada karyawan Perum Perhutani Divisi Regional Jawa Barat dan Banten) - Alfinia Salma Handayani; Suharnomo Suharnomo (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to analyze the effect of person-organization fit on employee turnover behavior with the role of organizational citizenship behavior as a moderating variable This study uses the person-organization fit as an independent variable, turnover intention as the dependent variable, and organizational citizenship behavior as a moderating variable. The population in this study were all active employees of Perum Perhutani Regional Division Jawa Barat and Banten, amounting to 126 people. This study takes the entire population as a sample or is called a census. Data obtained from questionnaires were processed and analyzed using SmartPLS programs. The results of the study show that person-organization fit has a positive effect on employee turnover intention, this can occur due to other factors such as age. The research also shows a positive and significant relationship between the person-organizational fit and organizational citizenship behavior. Other results show that organizational citizenship behavior negatively and significantly affects turnover intention. While the results of the mediating variable, that is organizational citizenship behavior, managed to become a variable that mediates between person-organizational fit and employee turnover intention.